Ligelizumab treatment for severe asthma: learnings from the clinical development programme. Issue 3 (15th March 2021) - Trischler, Jordis; Bottoli, Ivan; Janocha, Reinhold; Heusser, Christoph; Jaumont, Xavier; Lowe, Phil; Gautier, Aurelie; Pethe, Abhijit; Woessner, Ralph; Zerwes, Hans‐Günter; Zielen, Stefan
Abstract: Objective: Ligelizumab is a humanised IgG1 anti‐IgE antibody that binds IgE with higher affinity than omalizumab. Ligelizumab had greater efficacy than omalizumab on inhaled and skin allergen provocation responses in mild allergic asthma. This multi‐centre, randomised, double‐blind study was designed to test ligelizumab in severe asthma patients not adequately controlled with high‐dose inhaled corticoids plus long‐acting β2‐agonist. Methods: Patients received 16 weeks ligelizumab (240 mg q2w), omalizumab or placebo subcutaneously, and ACQ‐7 was measured as primary outcome at Week 16. In addition, the study generated dose‐ranging data of ligelizumab and safety data. Results: A total of 471 patients, age 47.4 ± 13.36 years, were included in the study. Treatment with ligelizumab did not significantly improve asthma control (ACQ‐7) and exacerbation rates compared to omalizumab and placebo. Therefore, primary and secondary objectives of the study were not met. The compound was well tolerated, and the safety profile showed no new safety findings. Pharmacokinetic data demonstrated faster clearance and lower serum concentrations of ligelizumab than historical omalizumab data, and exploratory in vitro data showed differential IgE blocking properties relative to FcεRI and FcεRII/CD23 between the two compounds. Conclusion: Ligelizumab failed to demonstrate superiority over placebo or omalizumab. Although ligelizumab is more potent than omalizumab at inhibiting IgE binding to the high‐affinity FcεRI, there is differential IgE blocking properties relative to FcεRI and FcεRII/CD23 between the two compounds. Therefore, the data suggest that different anti‐IgE antibodies might be selectively efficacious for different IgE‐mediated diseases. Abstract : In this multi‐centre, randomised, double‐blind study, 471 severe asthmatics were treated with the high‐affinity anti‐IgE antibody ligelizumab. Treatment did not significantly improve asthma control and exacerbations compared to omalizumab and placebo. Although ligelizumab is more potent than omalizumab at inhibiting IgE binding to the high‐affinity FcεRI, there is differential IgE blocking properties relative to FcεRI and FcεRII/CD23 between the two compounds, potentially blunting the effect in asthma.